2018
DOI: 10.1007/s00429-018-1651-z
|View full text |Cite
|
Sign up to set email alerts
|

Predicting personality from network-based resting-state functional connectivity

Abstract: Personality is associated with variation in all kinds of mental faculties, including affective, social, executive, and memory functioning. The intrinsic dynamics of neural networks underlying these mental functions are reflected in their functional connectivity at rest (RSFC). We, therefore, aimed to probe whether connectivity in functional networks allows predicting individual scores of the five-factor personality model and potential gender differences thereof. We assessed nine meta-analytically derived funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 154 publications
5
110
0
Order By: Relevance
“…Emerging evidence has suggested that multiple functional networks together constitute a domain‐general neural system subserving a wide range of psychological functions (Chanes & Barrett, ; Cole et al, ; Deco et al, ; Kleckner et al, ; Shine & Poldrack, ). Especially in the field of personality network neuroscience, researchers have proposed that the neurobiological basis of personality can be more comprehensively understood by capturing the brain‐wide interactions between distinct regions or large‐scale networks instead of a few local regions or single smaller‐scale circuits (Liu, Kohn, & Fernandez, ; Markett, Montag, & Reuter, ; Nostro et al, ). Similar to previous personality studies (Liu et al, ; Nostro et al, ), the level of NFC does not depend on the functional specificity of a single network but the result of the functional integration of multiple networks, which supports the emerging view above.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has suggested that multiple functional networks together constitute a domain‐general neural system subserving a wide range of psychological functions (Chanes & Barrett, ; Cole et al, ; Deco et al, ; Kleckner et al, ; Shine & Poldrack, ). Especially in the field of personality network neuroscience, researchers have proposed that the neurobiological basis of personality can be more comprehensively understood by capturing the brain‐wide interactions between distinct regions or large‐scale networks instead of a few local regions or single smaller‐scale circuits (Liu, Kohn, & Fernandez, ; Markett, Montag, & Reuter, ; Nostro et al, ). Similar to previous personality studies (Liu et al, ; Nostro et al, ), the level of NFC does not depend on the functional specificity of a single network but the result of the functional integration of multiple networks, which supports the emerging view above.…”
Section: Discussionmentioning
confidence: 99%
“…Recent large-sample neuroimaging studies have begun to explore these questions in some detail (Barch et al, 2013). These studies have investigated the contribution of demographic characteristics (Kharabian Masouleh et al, 2019;Smith et al, 2015), personality (Dubois et al, 2018;Nostro et al, 2018), intelligence (Cox et al, 2019), and cognitive function (Lerman-Sinkoff et al, 2017) to patterns of structural and functional connectivity. Much of this work has examined average connectivity patterns of activity derived from whole neuroimaging sessionsso-called "static" functional brain connectivity.…”
mentioning
confidence: 99%
“…Median Rank (MAD) r insula grayvol 1 (0) l insula grayvol 3 (1) l medialorbitofrontal grayvol 3 (2) r inferiorparietal area 4 (1) l temporalpole meancurv 8 (1) l insula myel 8 (5) l transversetemporal myel 11 (2) l precentral myel 12 (5) l rostralmiddlefrontal grayvol 13 (8) r precentral area 13 (11) From Figure 2c it is possible to find a clear trend in which a lower feature value help in a lower Sex-related factor or, in other words, to a brain looking more like a female one. It is also possible to see that the gray volumes of the insula in both hemispheres have a higher SHAP value, in magnitude, than any other feature which, adding to its median rank, shows how important that feature is in distinguishing male-and female-like brains.…”
Section: Brain Featurementioning
confidence: 99%